'It's Been an Absolute Nightmare' – Family Violence in Kinship Care in Victoria. (23rd February 2018) - Breman, Rachel; MacRae, Ann; Vicary, Dave
Abstract : Kinship care has become the fastest growing form of out-of-home care in Victoria and is the preferred placement option for children who are unable to live with their parents. Little is known about family violence in kinship care that is perpetrated by a close family member of the child in care (usually the child's mother/father) against the carer(s) and children once the placement has started. In this context, family violence means any act of physical violence, emotional/psychological violence, verbal abuse and property damage. In 2017, Baptcare undertook research with 101 kinship carers to gain a better understanding of how family violence was impacting on children and families in kinship care in Victoria. The study used a mixed design that specifically targeted kinship carers who had direct experience of family violence during their placement. This study has demonstrated that significant amounts of violence from family members are being experienced by kinship carers in Victoria and the children in their care. As a response to these findings, Baptcare is proactively addressing family violence in kinship care, across a range of domains, to provide solutions to the issues identified in this research.